A Geoinformatics-based Framework for Surface Water Quality Mapping and Monitoring - Japitana, M. V.; Burce, M. E. C.; Ye, C. (Engineering, Technology & Applied Science Research, 2019)
The management of water systems must be sustainable, something that requires systematic and comprehensive monitoring. However, the attempts to obtain a comprehensive water quality monitoring (WQM) program in developing countries are challenged due to the lack of an integrated framework and limited resources. At present, the Philippines has no systematized technical and operational monitoring approach, poor coordination and data collection system, and weak law enforcement. On the other hand, Geoinformatics promises a more convenient and cost-effective WQM to complement the traditional method. The goal of this study is to demonstrate how to maximize the use of Geonformatics in developing methods and models to address the lack of spatial trends, timely monitoring, and integrated monitoring framework that could lead to a sustainable WQM system. Results of this study showed that satellite images can be utilized to derive empirical models to estimate WQ parameters. The validation results showed that the estimated WQ values using the RS-based models have no significant difference when compared with the actual WQ values. Also, the WQ maps derived using Geographic Information System (GIS) were proven useful in providing better representation and analysis of spatial and temporal information that can provide a comprehensive and cost-effective reference for WQ monitoring and assessment.